Illicit drugs, metabolites and adulterants in wastewater : monitoring community drug abuse in the brazilian Federal District during the 2014 Soccer World Cup - Sodré, Fernando Fabriz (2017)
A multiresidue method was developed to estimate community drug use during two weekends of the 2014 Soccer World Cup via wastewater analyses. Five of the 16 investigated substances were detected in all eight samples. Benzoilecgonine (BE), the major cocaine metabolite, was the most abundant substance (1.9 ± 0.3 to 4.2 ± 0.2 μg L-1) followed by anhydroecgonine (AE) (1.5 ± 0.2 to 2.6 ± 0.2 μg L-1), phenacetin (PHE) (0.62 ± 0.06 to 1.3 ± 0.1 μg L-1), levamisole (LEV) (0.5 ± 0.2 to 1.23 ± 0.09 μg L-1), and cocaine (COC) (0.46 ± 0.07 to 0.8 ± 0.1 μg L-1). COC and BE levels suggested a human consumption origin for the investigated drugs. AE/BE ratios revealed a significant use of smoked crack/free base cocaine. Relationships between the adulterants PHE and LEV evidenced a higher use of crack cocaine in the South-Wing WWTP region. An estimative for cocaine use revealed slightly higher drug consumption during the Soccer World Cup weekends in comparison with a typical weekend in 2012.